Prevalência e distribuição de sorotipos de Aggregatibacter actinomycetemcomitans isolados de pacientes brasileiros com doença periodontal - Brígido, Jandenilson Alves (2012)
Studies suggest that subjects with severe periodontal lesions are more likely to colonize Aggregatibacter actinomycetemcomitans. This species is genetically heterogeneous and can be grouped into six serotypes (a-f), which may differ regarding virulence characteristics. Ethnic differences and geographic population can influence the distribution and prevalence of these serotypes regarding periodontal disease. The aims of this dissertation, comprised of two manuscripts, were to review the literature concerning A. actinomycetemcomitans serotypes regarding to periodontal status and geographic origin of individuals (chapter 1); and to investigate the prevalence and distribution of A. actinomycetemcomitans serotypes in Brazilian subjects with chronic and aggressive periodontitis, identifying possible relationship of the different A. actinomycetemcomitans serotypes with periodontal disease (chapter 2). In study 1 was performed a systematic review of the pertinent literature related to the issue and in study 2, subgingival plaque sample of 71 subjects with aggressive or chronic periodontitis positive to A. actinomycetemcomitans were analysed by polymerase chain reaction (PCR). The literature analysis presented in study 1 showed that different ethnic groups are preferentially colonized by different A. actinomycetemcomitans serotypes. Serotypes a, b and c were largely found, and serotype c was the most prevalent in the majority of studies. The results of study 2 demonstrated that serotype c was detected with the highest frequency and serotypes d-f were not detected. It was also observed that individuals with aggressive periodontitis showed higher prevalence of both serotypes b and c (p<0.05), and in chronic periodontitis subjects the serotype c was significantly more prevalent (p<0.05). In conclusion, the results of these studies suggest that the relationship between the different serotypes and periodontal conditions remains unclear (chapter 1). Serotype c was dominant among Brazilian subjects with periodontal disease and aggressive periodontitis subjects were associated both serotypes b and c (chapter 2).